Hydrogen production - Sequeira,César A. C. (2010)
Possible means of producing hydrogen are discussed. Emphasis is given on the electrolytic hydrogen production from water electrolysis, at large scale, via the use of renewable electricity (solar, wind, tidal, etc.). Its storage, transport and possible end-uses are also considered.